Peran dan intervensi pemerintah dalam perekonomian - Edy Suandi Hamid (Economic Journal of Emerging Markets, 1999)
It is widely accepted that government has an important role on economic development. Through policies on public sector for instance, government has a significant role in pushing economic growth. However, in economics literatures, there seems a debate about whether government should role on economic development.